Superconductivity in bcc-selenium under megabar pressure - Zhongyan Wu; Timofey Fedotenko; Nico Giordano; Jaeyong Kim (Scientific Reports)
Abstract We report enhanced superconductivity in the selenium on the verge of the β-Po–bcc phase transition, achieving up to 9.4 K at 140 GPa. The onset of superconductivity is confirmed by a direct zero-resistance drop R(T), and its nature was further validated by its suppression under an external magnetic field, $$\:{μ\:}_{0}{H}_{c}\left(0\right)=0.26\:{\text{T}}$$ at 140 GPa. An anomalously high R(T) peak preceding the zero resistance state suggests granular superconductivity. Our studies indicate that selenium does not react with hydrogen at 182 GPa at room temperature nor 102 GPa with laser heating to 3000 K, implying that the synthesis of selenium hydride requires higher energy conditions than the ones predicted theoretically. Our findings offer insights into the mechanism of phase-transition-related enhanced superconductivity and motivate further study into the search for high $$\:T_{c}$$ superconductors in elements at extremely high pressure.